Women of courage - Truman, Margaret, 1924- (New York : Morrow, 1976)
Brief biographies emphasizing the courage of twelve women both famous and little-known in United States history.
Includes index.
2 3 11 13 20 26 31 33 36
Keywords: Women -- United States -- Biography; United States -- Biography